APPLICATION OF LARGE LANGUAGE MODELS IN OPTIMIZING THE E-RECRUITMENT PROCESS - Doskach, Denys; Khavalko, Viktor (Herald of Khmelnytskyi National University. Technical sciences, 2024)
This article delves into the transformative impact of Large Language Models (LLMs) on automating tasks and creating smart tools. As a key development in artificial intelligence, LLMs have grown from basic statistical models to complex systems that can mimic how humans process language. This growth shows their flexibility and potential to change how things are done in various areas, especially in software engineering and recruitment. It starts with a look at how LLMs have developed over time, moving from simpler models to advanced ones like GPT-3, which can understand and create language in ways that didn't require special adjustments.The discussion then moves to what LLMs can do now, emphasizing their new skills in learning from context and solving problems. These abilities are a big step forward, allowing LLMs to work with more than just text and opening up new possibilities for AI use. The article uses real-life examples to show how LLMs are being used in different fields. It talks about using natural language to control drones, making it easier for people to interact with robots, and LLM-based recruitment tools that improve job matching by extracting and organizing skills from resumes and job descriptions.Looking ahead, the article talks about the future of LLM development, focusing on efforts to give these models more human-like abilities to understand and interact with the world, and to make them more efficient. This future promises AI that can interact with the world in ways closer to how humans do, making AI more intuitive and effective. Yet, it also points out the challenges, including the need for LLMs to be powerful yet efficient, understandable, and ethically used.In concluding, the article highlights LLMs as both a symbol of progress and a complex area that needs careful consideration to fully and responsibly use their capabilities. This overview offers valuable information for those involved in AI, giving insights into current LLM applications and directions for future research in this exciting area.
Keywords: Large Language Models, Artificial Intelligence, Natural Language Processing, e-recruitment